Computational Fluid Dynamics Analysis of Compressible Flow Through a Converging-Diverging Nozzle using the k-ε Turbulence Model - Khalid, M. W.; Ahsan, M. (Engineering, Technology & Applied Science Research, 2020)
The thrust produced by a rocket motor is mainly dependent upon the expansion of the product gases through a nozzle. The nozzle is used to accelerate the gases produced in the combustion chamber and convert the chemical-potential energy into kinetic energy so that the gases exit the nozzle at very high velocity. It converts the high pressure, high temperature, and low-velocity gas in the combustion chamber into high-velocity gas of lower pressure and low temperature. The design of a nozzle has particular importance in determining the thrust and performance of a rocket. In recent years, it has received considerable attention as it directly impacts the overall performance of the rocket. This paper aims to analyze the variation of flow parameters like pressure, Mach number, and velocity using Finite Volume Method (FVM) solver with the standard k-ε turbulence model in Computational Fluid Dynamics (CFD). The simulation of shockwave inside the divergent nozzle section through CFD is also investigated. In this regard, a nozzle has been designed using Design Modeler, and CFD analysis of flow through the nozzle has been carried out using ANSYS Fluent. The model results are compared with theoretically calculated results, and the difference is negligible.